2014
DOI: 10.1111/imb.12109
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of sex pheromone receptors in the purple stem borer, Sesamia inferens (Walker)

Abstract: The sex pheromone communication system in moths is highly species-specific and extremely sensitive, and pheromone receptors (PRs) are thought to be the most important factors in males. In the present study, three full-length cDNAs encoding PRs were characterized from Sesamia inferens antennae. These three PRs were all male-specific in expression, but their relative expression levels were very different; SinfOR29 was 17- to 23-fold higher than the other two PRs. Phylogenetic and motif pattern analyses showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…In addition, we identified 4 candidate PR genes by sex expression and physiologic analysis. One PR (AlepOR6) was detected in both male and female antennae; this result which was similar to that of SlitEZ981960 and SlitFQ031000 of S. littoralis (Legeai et al, 2011), HarmOR6 and HarmOR13 of H. armigera , and SinfOR21, 27, and 29 of S. inferens (Zhang et al, , 2014. Similarly, BmorOR19 and BmorOR30 of B. mori (Wanner et al, 2007), HarmOR5 and HarmOR21 of H. armigera , SinfOR16 of S. inferens , and AlepOR45 of A. lepigone displayed femalespecific expression.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, we identified 4 candidate PR genes by sex expression and physiologic analysis. One PR (AlepOR6) was detected in both male and female antennae; this result which was similar to that of SlitEZ981960 and SlitFQ031000 of S. littoralis (Legeai et al, 2011), HarmOR6 and HarmOR13 of H. armigera , and SinfOR21, 27, and 29 of S. inferens (Zhang et al, , 2014. Similarly, BmorOR19 and BmorOR30 of B. mori (Wanner et al, 2007), HarmOR5 and HarmOR21 of H. armigera , SinfOR16 of S. inferens , and AlepOR45 of A. lepigone displayed femalespecific expression.…”
Section: Discussionsupporting
confidence: 70%
“…In particular, we found that AlucOR91 were highly expressed in the female antennae (7.4 times higher than in other tissues) and AlucOR21 in the male antennae (38.1 times higher than in other tissues), indicating sex-specific functions of AlucOR91 and AlucOR21 . According to previous studies of the insect OR functions in moths4041424344, the male-dominant expression of ORs might be involved in the detection and discrimination of the sex pheromone or in other male-specific behaviors, while female-dominant expression of ORs might have the preferential function that is critical to female olfactory behavior, such as oviposition sites selection or male-produced courtship pheromones detection. The sex-specific functions of these ORs need to be further investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, functional characterization of insects’ OR has been successfully conducted using heterologous systems [24,25,26,27]. When expressed in Xenopus oocytes, AlucOR46 was tuned to six plant volatiles, with stronger responses and higher sensitivity to ( E )-2-Hexenal, ( E )-3-Hexenol, 1-Heptanol and ( 1R )-(−)-Myrtenol.…”
Section: Discussionmentioning
confidence: 99%